Effect of Different Media and pH on Mycelial Growth of Sclerotium oryzae Causing Sheath Rot of Rice - Ahmad, Md Iqbal; Biswas, Avijit Kumar; Sultana, Mst Sabiha; Sarker, Bidhan Chandro; Mondal, Chhoa (South Asian Journal of Agriculture, 2019)
Sclerotium oryzae causing sheath rot of rice, is one of the most important pathogen causing heavy crop losses in all the major rice growing areas of the world, including Bangladesh. The growth and reproduction of this soil borne pathogen depends on growing media and abiotic factors. Therefore, to evaluate the effect of different culture media and pH on mycelial radial growth of S. oryzae, the experiment was conducted in the Plant Pathology Laboratory of Agrotechnology Discipline, Khulna University, Khulna, Bangladesh. Performance of different media, carbon source and nitrogen source on radial mycelial growth was differed significantly. The maximum mycelial radial growth was observed on rice stem agar medium (70.40 mm) and minimum mycelial radial growth was recorded on cornmeal agar medium (50.60 mm). Considering carbon source, the maximum radial mycelial growth was found in glucose (66.40 mm) amended medium and no statistical differences were observed among sucrose, starch and Czapek dox agar containing medium. Based on nitrogen source, maximum radial mycelial growth was found in peptone medium (69.40 mm) but no statistical differences were exposed between Potassium nitrate (KNO3) and Sodium nitrate (NaNO3). pH- 6 played a vital role in radial mycelial growth (73.75 mm) of S. oryzae. South Asian J. Agric., 7(1&2): 67-72